Benzothiadiazole‐Substituted Aza‐BODIPY Dyes: Two‐Photon Absorption Enhancement for Improved Optical Limiting Performances in the Short‐Wave IR Range. Issue 10 (25th January 2021) - David, Sylvain; Chang, Hao‐Jung; Lopes, Cesar; Brännlund, Carl; Le Guennic, Boris; Berginc, Gérard; Van Stryland, Eric; Bondar, Mykailo V.; Hagan, David; Jacquemin, Denis; Andraud, Chantal; Maury, Olivier
Abstract: Aza‐boron dipyrromethenes (aza‐BODIPYs) presenting a benzothiadiazole substitution on upper positions are described. The strong electron‐withdrawing effect of the benzothiadiazole moiety permits enhancement of the accepting strength and improves the delocalization of the aza‐BODIPY core to attain a significant degree of electronic communication between the lower donating groups and the upper accepting groups. The nature of the intramolecular charge transfer is studied both experimentally and theoretically. Linear spectroscopy highlighted the strongly redshifted absorption and emission of the synthesized molecules with recorded fluorescence spectra over 1000 nm. Nonlinear optical properties were also investigated. Strong enhancement of the two‐photon absorption of the substituted dyes compared with the unsubstituted one (up to 4520 GM at 1300 nm) results in an approximately 15–20 % improvement of the optical power limiting performances. These dyes are therefore a good starting point for further improvement of optical power limiting in the short‐wave IR range. Abstract : Improved optical limiting performances : Benzothiadiazole moieties act as powerful electron‐withdrawing auxiliaries enforcing the accepting character of aza‐BODIPY dyes and resulting in a significant redshift of both absorption and emission and a remarkable enhancement of the nonlinear optical properties (two‐photon absorption and optical limiting) compared with traditional aryl substituents.